2021
DOI: 10.1126/scitranslmed.abj9837
|View full text |Cite
|
Sign up to set email alerts
|

Developing nociceptor-selective treatments for acute and chronic pain

Abstract: Phenotypic screens using human induced pluripotent stem cell–derived nociceptors hold promise for the development of better analgesics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 254 publications
0
34
0
Order By: Relevance
“…Pluripotent and differentiating cells, harvested at different timepoints, were compared to adult human DRG samples. Since pain is associated with structural and functional plasticity 7 , we also included tissue samples obtained from individuals with a clinical history of chronic pain. PCA plots showed that DRG samples clustered together and were distinct from cultured cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pluripotent and differentiating cells, harvested at different timepoints, were compared to adult human DRG samples. Since pain is associated with structural and functional plasticity 7 , we also included tissue samples obtained from individuals with a clinical history of chronic pain. PCA plots showed that DRG samples clustered together and were distinct from cultured cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nociceptor-selective sodium channels are promising targets to develop new analgesics 7,39 . To test whether hPSC-derived nociceptors could be used in high-throughput fashion, we performed a functional screen using an automated patch-clamp system (Qube 384, Sophion Bioscience).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the use of induced pluripotent stem cell (iPSC)-derived neurons for compound screening is a promising approach to identify novel analgesics [ 112 ]. For example, disease modeling using iPSC-derived neurons from persistent pain patients could be used to identify common pathophysiological alterations that may be responsible for the pain state of subgroups of patients.…”
Section: Discussionmentioning
confidence: 99%